2021
DOI: 10.1186/s40635-021-00401-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive end-expiratory pressure on additional passive ventilation generated by CPR compressions in a porcine model

Abstract: Background Compressions given during cardiopulmonary resuscitation generate small, ineffective passive ventilations through oscillating waves. Positive end-expiratory pressure increases the volume of these passive ventilations; however, its effect on passive ventilation is unknown. Our objective was to determine if increasing positive end-expiratory pressure during cardiopulmonary resuscitation increases passive ventilation generated by compressions to a clinically significant point. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, when using PEEP, increased oxygenation could be observed in this trial. A study that investigated whether different PEEP levels could optimise carbon dioxide clearance during CPR showed that higher PEEP levels lead to significantly decreased paCO 2 levels and increased minute volume because of a higher fraction of gas oscillations generated by chest compressions [ 17 ]. However, this study intentionally did not adhere to resuscitation guidelines regarding respiratory rates, partially explaining these results and potentially reducing their clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…However, when using PEEP, increased oxygenation could be observed in this trial. A study that investigated whether different PEEP levels could optimise carbon dioxide clearance during CPR showed that higher PEEP levels lead to significantly decreased paCO 2 levels and increased minute volume because of a higher fraction of gas oscillations generated by chest compressions [ 17 ]. However, this study intentionally did not adhere to resuscitation guidelines regarding respiratory rates, partially explaining these results and potentially reducing their clinical relevance.…”
Section: Discussionmentioning
confidence: 99%